Rumen volatile fatty acids and morphology of the rumen mucosa of swamp buffalo raised under semi-intensive and extensive system in tropical environment - Mat Amin, Fhaisol; Mohd Azmi, Amirul Faiz; Idris, Lokman Hakim; Abu Hassim, Hasliza; Saad, Mohd Zamri; Abu Bakar @ Zakaria, Md Zuki (Universiti Putra Malaysia Press, 2022)
Swamp buffaloes are mostly raised under an extensive system because they can adapt to the harsh environment. However, exploring the rumen mucosa (RM) morphology and volatile fatty acids (VFA) of swamp buffalo associated with different production systems is still lacking. This study evaluated the rumen VFA and morphology of RM between two groups of buffalo raised under semi-intensive (SI) and an extensive system (EX). VFA was analysed using gas chromatography. The morphology of rumen mucosa was evaluated macro and microscopically for papillae length and width, surface area, density, and muscle thickness, and the microscopic evaluation for stratified squamous epithelium (SSE) and keratin thickness. SI has a greater VFA concentration than the EX. The SSE layer on the dorsal region of the rumen was thicker in the EX group than in the SI group (p≤0.05). Within the group, the SSE of the dorsal region of rumen was thicker than the ventral region (p≤0.05) in the EX group. However, the ventral region of the rumen was thicker than the dorsal region in the SI group. The thickness of the keratin layer in the EX group was significantly thicker than the SI group (p≤0.05) only on the dorsal region. In conclusion, swamp buffalo from the SI production system has a greater concentration of volatile fatty acid than the EX-group contributed by feeding management under a semi-intensive system. Nevertheless, the advantage in VFA concentration alone is not sufficient to conclude semi-intensive production system exerts a favourable effect on the morphology of the rumen mucosa.